The Revival of SMEs in Indonesia from The Impact of The Covid-19 Pandemic - Edy Prayitno; Nerys Lourensius L. Tarigan; Uyuunul Mauidzoh; Wahyu Eka Priana Sukmawaty (AIBPM Publisher, 2024)
This research examines the revival of Small and Medium Enterprises (SMEs) in Indonesia facing the COVID-19 pandemic. This pandemic presents major challenges and is a catalyst for unprecedented change in the SME sector. This article aims to identify and analyze the main factors that play a role in the resilience and growth of Indonesian SMEs during and after the pandemic. Through a mixed methods approach, utilizing quantitative data and qualitative interviews, this research reveals that digital transformation, government stimulus, and community solidarity play an important role. The research results show that SMEs that use digital marketing show good adaptability and growth, and benefit from the shift in consumer behavior to online platforms. The Indonesian government's fiscal support by assisting struggling SMEs, enables business continuity and recovery from the impact of the pandemic. Additionally, the role of community-based initiatives in fostering collective resilience is also a unique aspect of the business landscape in Indonesia. The study concludes with policy recommendations to maintain the growth and resilience of SMEs, emphasizing the importance of digital inclusion, easy access to financial institutions, and community support networks. The impact of this research is significant for policymakers, business leaders, and community developers aiming to protect the SME sector from future crises.